Goal attainment, adjustment and disengagement in the first year after stroke: A qualitative study. Issue 5 (28th May 2021) - Scobbie, L.; Brady, M. C.; Duncan, E. A. S.; Wyke, S.
ABSTRACT: Understanding stroke survivor responses to attainable and unattainable goals is important so that rehabilitation staff can optimally support ongoing recovery and adaption. In this qualitative study, we aimed to investigate (i) stroke survivor's experiences of goal attainment, adjustment and disengagement in the first year after stroke and (ii) whether the Goal setting and Action Planning (G-AP) framework supported different pathways to goal attainment. In-depth interviews were conducted with eighteen stroke survivors' to explore their experiences and views. Interview data were transcribed verbatim and analysed using a Framework approach to examine themes within and between participants. Stroke survivors reported that attaining personal goals enabled them to resume important activities, reclaim a sense of self and enhance emotional wellbeing. Experiences of goal-related setbacks and failure facilitated understanding and acceptance of limitations and informed adjustment of, or disengagement from, unattainable goals. Use of the G-AP framework supported stroke survivors to (i) identify personal goals, (ii) initiate and sustain goal pursuit, (iii) gauge progress and (iv) make informed decisions about continued goal pursuit, adjustment or disengagement. Stroke survivor recovery involves attainment of original and adjusted or alternative goals. The G-AP framework can support these different pathways to goal attainment.